AROMATHERAPY OIL MASSAGE FORMULATION FROM ESSENTIAL OIL: TUBEROSE FLOWER (Polianthes tuberosa) AND LIME OIL (Citrus aurantifolia) - Andrew Setiawan Rusdianto; Andi Eko Wiyono; Felly Halsa Fiana (International Journal on Food, Agriculture and Natural Resources, 2020)
Aromatherapy is a therapy that utilizes steam from the essential oils of certain plants. Essential oils are oils produced from plant parts, such as roots, bark, stems, flowers, leaves, and seeds that have volatile properties at room temperature without undergoing decomposition by means of distillation. This study aims to determine the effect of a comparison of the concentration level of essential oils on physical properties and consumer preferences and to find out the aromatherapy massage oil formulation that produces the best massage oil. This study uses a completely randomized design (CRD) with 1 factor, namely the difference in the ratio of the essential oil of the nightly flower to the essential oil of lime. The experiment was carried out 2 times. The usual dilution was 1 ml of essential oil in 50 ml of carrier oil. The treatments are P1 (0.2 ml of nightly essential oil: 0.8 ml of lime essential oil), P2 (0.4 ml of nightly essential oil: 0.6 ml of lime essential oil), P3 (0.5 ml nightly essential oils: 0.5 ml lime essential oil, P4 (0.6 ml nightly essential oils: 0.4 ml lime essential oil), and P5 (0.8 ml nightly essential oils), 2 ml of lime essential oil). The parameters observed were pH, specific gravity, viscosity, refractive index, color, and hedonic test.